Análisis jurídico del proceso administrativo de la adopción en el Estado Ecuatoriano. - Poma Jiménez, Paula Ivannova (2023)
This research work entitled "Legal Analysis of the Administrative Process of Adoption in the Ecuadorian State" is aimed at carrying out a dogmatic and legal study of the administrative process contemplated in Ecuadorian regulations, which must be carried out to proceed with the adoption of minors of age, before the judge legally resolves the adoption. The situation of orphanage of hundreds of minors brings with it serious social consequences, since they are vulnerable people who become easy prey for criminal groups; even more desirable for being unimputable before the state criminal justice system; Another situation in this regard is that reception centers are not appropriate for the development and upbringing of children and adolescents. The Ecuadorian State, like one hundred percent of the laws in the world, contemplates the legal institution of adoption as a solution to the social problems that derive from orphanhood; this institution is legally contemplated, but there is an administrative process that requires a number of requirements, procedures and documents that bureaucratize it in an exaggerated way; the procedures are delayed in annual periods that cause the withdrawal of couples interested in giving a home to orphaned minors. The adoption process seeks to guarantee a suitable, permanent and definitive family for the girl, boy or adolescent who is in legal and social aptitude to be adopted, this is why it is necessary to legally and administratively determine where the critical knots are located in the adoption processes, so that they do not have a successful end. It is necessary to carry out an analysis from the perspective of the doctrine, supported by the legal regulations of adoption and its procedure in state institutions, complemented by an exhaustive study of requirements and situations that occur during the procedure. 5 In this investigation I seek to determine the importance of establishing certain times in the process of the administrative phase, eradicating the current problem, in which said process becomes chaotic and delayed procedures that make minors in the state of adoption unprotected and without family stability that legally grants them the protection and economic and emotional stability that the natural family could not give them. The problem that is generated is that abandoned children do not find a real family, due to administrative procedures that are too bureaucratic. The research methodology is of a qualitative type, with the dogmatic and interpretative method of the constitutional and legal norm, since through these methods an answer to the problem treated is offered based on what is believed to be the best possible reconstruction allowed by the legal material available; in addition, the facts or social phenomena studied in this work are measurable and quantifiable. I will measure and establish causal relationships between the variables, to explain the study problem and the current social reality. Keywords: Administrative Process, Adoption, Due Process, Best Interest of the Child, Celerity, Debureaucratization.